Development of a Citrus Drink Using Mixture Design: Sensory Evaluation, Total Polyphenols and Vitamin C - Jeimison Bazán-Plasencia; Antony Mejía-Vásquez; Gerald H. Bracamonte; Juanita Anali Ponce-Ramirez; Ronald Ortecho-Llanos; Beetthssy Z. Hurtado-Soria; Eudes Villanueva; Elza Aguirre (Beverages)
The development of beverages with functional potential and maximum sensory acceptability are priorities for the food industry. This study investigated the effect of orange juice (OJ), lemon juice (LJ) and ginger juice (GJ) concentrations on overall acceptability (OA), total phenic compounds (TPC) and vitamin C (VC). The experimental design used was simplex-centroid mixtures, and maximization was achieved using response surface methodology (RSM). The bioactive content of TPC and VC was measured using the Folin–Ciocalteu method and the dichlorophenol indophenol method, respectively; sensory evaluation was conducted with 100 panelists on a continuous scale acceptability primer (0–10 points). The RSM results indicated that the optimum formulation was obtained with: OJ = 79.8 mL, LJ = 5.7 mL and GJ = 4.37 mL, yielding maximum values of OA = 6.81 points, TPC = 14.64 mg GAE/100 g and VC = 32.3 mg/mL. The optimized beverage presented a free radical scavenging capacity of 65.72% (DPPH method). The regression models were validated and significantly (p < 0.05) predicted sensory acceptability, total phenolic compounds and vitamin C content. The development of this beverage and its potential application in the food industry is attractive due to its high sensory acceptability and bioactive content.